DETERMINAN RISIKO BANK DI INDONESIA - Cici Widowati; Najiba Dara Ninggar; Raden Arief Wibowo (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2021)
This study investigates the relationship between deposits growth (DG), bank capital (TIER1), credits growth (CG), loan loss provision to asset (LLPA), net interest margin (NIM), and bank risk which proxied by SDROA, SDROE, and ZSCORE. The analysis in this paper uses 11 samples of listed banks in Indonesia Stock Exchange (IDX), which are carried out at the annual level from 2006 to 2018. The results indicate that the influence of bank capital (TIER1), credits growth (CG), and loan loss provision to asset (LLPA), are always persistent and significant. According to the results of this paper, the influence of deposits growth (DG), bank capital (TIER1), and credits growth (CG), on bank risk, tends to be negative since the bank risk proxy is SDROA or SDROE, while the influence of loan loss provision to asset (LLPA) and net interest margin (NIM), on bank risk, tends to be positive since the bank risk proxy is ZSCORE. However, the result of this study also shows that bank risk proxies do react differently to the determinants of bank risk.